What Is Your Biggest Pain Point? An Investigation of CS Instructor Obstacles, Workarounds, and Desires - Mirhosseini, Samim; Henley, Austin Z.; Parnin, Chris (SIGCSE '23: ACM Technical Symposium on Computer Science Education, 2023)
Computer science instructors have one of the most crucial roles in training and making educational materials. However, they face many challenges everyday that make it difficult to provide a high-quality learning experience to their students. Additionally, trends in demand for computer science training is rapidly increasing and to meet this demand, classrooms need to run on a larger scale, which may exacerbate instructor pain points further. While many of the previous studies in the computer science education community have focused on how to improve the students' learning experience, in this study we investigate computer science instructors. It is paramount to understand how instructors can be supported more effectively while continuing to improve the material they use in their courses and allow them to focus on student needs. To understand these instructor challenges, we conducted semi-structured interviews with 32 computer science instructors at universities and community colleges to ask about their experiences in preparing course material, lecturing, grading, providing feedback to students, and what they wished they could change. In this paper, we summarize our findings as themes of challenges and pain points for instructors, the consequences of not solving them, and suggested guidelines that may help resolve or reduce these pain points.